International Internship Students’ Interventions toward Islamic School Teachers’ English Proficiency - Jupri (EDUCAFL: Journal on Education of English as Foreign Language, 2025)
This study aimed to enhance the English-speaking proficiency, self-confidence, and vocabulary knowledge of Islamic school teachers at Yayasan Pondok Pesantren Alhamidiyah NW Sidemen, Batulayar District, West Lombok, West Nusa Tenggara. The program involved five international internship students from Saxion University, the Netherlands, who served as tutors in a four-month intervention. Employing a mixed-methods approach, the study adopted direct role-play activities in which the international students acted as school principals and used English as the main medium of communication four times per week. Participants included twenty teachers and five staff members from elementary, junior high, and senior high school levels. Quantitative and qualitative data were collected to examine changes in teachers’ speaking activity, confidence, and vocabulary use. The findings indicate a substantial improvement in teachers’ participation in English communication, beginning with basic greetings and progressing to interactive responses. Teachers’ self-confidence increased markedly, as reflected in their enthusiasm and willingness to compete in responding during the role-play sessions. Vocabulary knowledge also improved, evidenced by the growing frequency and variety of teachers’ responses. Overall, formerly passive teachers demonstrated behavioral change toward more active engagement. The study concludes that the direct involvement of international internship students through sustained role-play activities effectively contributes to improving Islamic school teachers’ English proficiency.